ANALISIS PENYUSUNAN ANGGARAN BIAYA OPERASIONAL CV. SUKSES BERSAMA - Asih Nur’aidah; Nadya Ayu Puspita; Nisya Z Nurwulan Sari; Rachmat Agus Santoso (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
Budgeting is one way to reduce costs. With a budget, the company can control the company’s expenses. Budgeting for company expenses is an important aspect of a company’s efforts to reduce costs. To obtain good result from efforts to reduce costs, the budget preparation process must be carried out well. The aim of this research is to determine the extent to which the operational cost budget can help management in measuring the company’s operational cost. The analytical method used in this research is a qualitative descriptive method where the data collected is based on the results of interviews with respondents regarding the research and comparing it with theories and rules that are relevant to the research issue. The research results show that the budget is a limitation for budget users in proposing budget realization. With the preparation of a budget, budget users cannot be arbitrary in spending costs. Therefore, the budget really helps company management in measuring the efficiency of the company’s operational costs.